2009
DOI: 10.1109/tcomm.2009.12.080318
|View full text |Cite
|
Sign up to set email alerts
|

Turbo packet combining strategies for the MIMO-ISI ARQ channel

Abstract: This paper addresses the issue of efficient turbo packet combining techniques for coded transmission with a Chase-type automatic repeat request (ARQ) protocol operating over a multiple-input-multiple-output (MIMO) channel with intersymbol interference (ISI). First of all, we investigate the outage probability and the outage-based power loss of the MIMO-ISI ARQ channel when optimal maximum a posteriori (MAP) turbo packet combining is used at the receiver. We show that the ARQ delay (i.e., the maximum number of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…It presents an extension of the turbo packet combining methods initially proposed for conventional broadband ARQ systems [16], [17] to relay communications.…”
Section: A Brief Overview Of the Conceptmentioning
confidence: 99%
“…It presents an extension of the turbo packet combining methods initially proposed for conventional broadband ARQ systems [16], [17] to relay communications.…”
Section: A Brief Overview Of the Conceptmentioning
confidence: 99%
“…We introduce two packet combining where all ARQ rounds are used jointly to decode the data packet. The first packet combining scheme, referred to as chip-level packet combining scheme, is an extension of the combining approach introduced in [11,13] to the case of multi-antenna multi-code CDMA systems. In this combining scheme, we exploit the fact that both the CP chip-word and data packet are retransmitted at each ARQ round.…”
Section: Introductionmentioning
confidence: 99%
“…The diversitymultiplexing-delay tradeoff has then been characterized in the case of block-fading MIMO ARQ channels, i.e., multiple fading blocks are allowed within the same ARQ round [25]. In [26], the outage probability of MIMO-ISI ARQ channels has been evaluated under the assumptions of short-term static channel dynamic 2 , and Chase-type ARQ [27], i.e., the data packet is entirely retransmitted. It has been shown that, as in the flat fading case, ARQ presents an important source of diversity, but its influence becomes only minimal when the 1 In non-ergodic, i.e., block fading quasi-static channels, the outage probability is a meaningful measure that provides a lower bound on the block error probability.…”
Section: Introductionmentioning
confidence: 99%
“…[28], [29], [30], [31], [32], [33], [34], [35], [36]). Turbo combining techniques, where decoding is iteratively performed through the exchange of soft information between the soft-input-soft-output (SISO) packet combiner and the SISO decoder, have been proposed for the MIMO-ISI ARQ channel using unconditional minimum mean square error (MMSE)-aided combining [37], [26]. These approaches have then been extended to broadband MIMO code division multiple access (CDMA) systems with ARQ [38].…”
Section: Introductionmentioning
confidence: 99%